Potential Of Red Shoot Leaf Extract (Syzygium oleina) as An Antifungi Against The Growth of Sclerotium rolfsii in vitro - Kartika Sari; Linda Advinda; Azwir Anhar; Moralita Chatri (Jurnal Serambi Biologi, 2022)
Sclerotium rolfsii is type pathogenic fungus that can cause diseases in plants such rot on tstem, wilting and sprouts. S. rolfsii includes soil tular fungal that can last a long time the form of sclerotia the soil, manure, and the remains sick plants. Control can be developed the use synthetic fungicides, but these fungicides can have a negative impact the environment. Then is necessary to control the environment, namely by using vegetable fungicides because they come from plants. Like red shoot leaf extract (Syzygium oleina). Red shoot plants contain many secondary metabolite compounds such flavonoids, tannins and alkaloids that are antimicrobial in nature. This study aims to look at the potential red shoot leaf extract against the growth S. Rolfsii and the antifungal activity red shoot leaves against growth S. rolfsii. The research conducted from February to April 2022 at the Research Laboratory the Department of Biology, Faculty of Natural Sciences, Padang State University. This study is an experimental study with 5 treatments and 3 repetitions. Treatment using red shoot extract. Concentrations 10%, 20%, 30%, and 40% and control (0%) using solvent aquades. The results showed that red shoot leaf extract has the potential to inhibit the growth S. rolfsii.